Семантико-когнитивный метод выявления знаний глоссария - Петрасова, Светлана Валентиновна (Харківський національний університет радіоелектроніки, 2014)
The given work is devoted to the method of the automatic construction of the domain semantic network on the basis of glossary knowledge as the most concentrated natural language text. In this work, the cognitive paradigm of the identification of implicit relations’ category of equivalence using factorization of concepts’ domain has been considered. Patterns of lexical sets have been used for the formalization of the explicit categories of concepts’ relations of the semantic network such as belonging to the class, hypernymy, hyponymy and myronymy.
Keywords: интеллектуальные информационные системы; знания; семантические сети; лексические последовательности